Depression and Psychosocial Stress Are Associated With Subclinical Carotid Atherosclerosis Among Women Living With HIV. Issue 13 (7th July 2020) - Levy, Matthew E.; Anastos, Kathryn; Levine, Steven R.; Plankey, Michael; Castel, Amanda D.; Molock, Sherry; Sen, Sabyasachi; Asch, Federico M.; Milam, Joel; Aouizerat, Bradley; Weber, Kathleen M.; Golub, Elizabeth T.; et al.
Abstract : Background: To identify reasons for increased atherosclerotic risk among women living with HIV (WLWH), we evaluated the associations between psychosocial risk factors (depressive symptoms, perceived stress, and posttraumatic stress disorder symptoms) and subclinical atherosclerosis among WLWH and HIV‐negative women. Methods and Results: Carotid artery focal plaque (localized intima‐media thickness >1.5 mm) was measured using B‐mode ultrasound imaging in 2004–2005 and 2010–2012 in the Women's Interagency HIV Study. We created psychosocial risk groups using latent class analysis and defined prevalent plaque at the final measurement. We also examined repeated semiannual depression measures with respect to focal plaque formation throughout follow‐up. The associations between latent class and prevalent plaque, and between depressive symptom persistence and plaque formation, were assessed separately by HIV status using multivariable logistic regression. Among 700 women (median age 47 years), 2 latent classes were identified: high (n=163) and low (n=537) psychosocial risk, with corresponding prevalence of depression (65%/13%), high stress (96%/12%), and probable posttraumatic stress disorder (46%/2%). Among WLWH, plaque prevalence was 23% and 11% in high versus low psychosocial risk classes (adjusted odds ratio [aOR], 2.12; 95% CI, 1.11–4.05) compared with 9% and 9% among HIV‐negative women (aOR, 1.07; 95% CI, 0.24–4.84), respectively. New plaque formation occurred among 17% and 9% of WLWH who reported high depressive symptoms at ≥45% versus <45% of visits (aOR, 1.96; 95% CI, 1.06–3.64), compared with 9% and 7% among HIV‐negative women (aOR, 0.82; 95% CI, 0.16–4.16), respectively. Conclusions: Psychosocial factors were independent atherosclerotic risk factors among WLWH. Research is needed to determine whether interventions for depression and psychosocial stress can mitigate the increased risk of atherosclerosis for WLWH.